Investigation of Historical Extreme Rainfall on Permeable Road in a Commercial Centre - Darrien Yau Seng, Mah; Dayang Nur Huwaida, Abang Sulaiman; Teo, Fang Yenn (University of Biskra, Algeria, 2023)
Urban development areas, having greater impervious surfaces such as roads, parking spaces and building roofs, have an adverse impact on the urban environment, as they generate more runoff. This situation could even worsen during extreme rainfall events as it accumulates stormwater runoff more rapidly and causes the occurrence of flash floods. In this study, eight historical extreme rainfall events with rainfall depths between 40 and 70 mm were chosen to investigate the performance of permeable pavement as an urban runoff mitigation measure approach in stormwater management. A commercial center was selected as a case study, with a total catchment area of 3,425 m2 and consisting of double-row roadside car parking spaces with tarred surfaces covering 61% of the total catchment area. The front road of the shophouses was assumed to be replaced with a modular-based precast stormwater detention system, and a drainage model was developed to mimic the system. Simulations of the stormwater flowing through the detention system were performed with Storm Water Management Model version 5.0, and it was found that the detention system could endure seven out of the eight storms. The only storm that overwhelmed the system demonstrated an intense rainfall pattern that peaked in the first hour.